2020
DOI: 10.1039/d0tc03770b
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive properties study of low-temperature imidized polyimide with curing accelerators

Abstract: Low temperature curing polyimide (PI) has become a significant target for the advanced electronic package recently. Even though curing accelerators which could significantly reduce the curing temperature have been proved,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…The initial poly(amic acid) synthesis was performed in NMP at room temperature. Quinoline was added to the reaction mixture to serve as an imidization accelerator, 46 allowing the conversion to imide to occur at lower temperatures, and the reaction was heated to 180 °C with the removal of water as a toluene azeotrope to produce PEI‐PDADMA(PF 6 ). Copolymer compositions were determined by integrating the characteristic DADMA(PF 6 ) peaks and comparing values to those of the methyl proton peaks from the BPA‐type linkages (Figures 6 and S22–S24).…”
Section: Resultsmentioning
confidence: 99%
“…The initial poly(amic acid) synthesis was performed in NMP at room temperature. Quinoline was added to the reaction mixture to serve as an imidization accelerator, 46 allowing the conversion to imide to occur at lower temperatures, and the reaction was heated to 180 °C with the removal of water as a toluene azeotrope to produce PEI‐PDADMA(PF 6 ). Copolymer compositions were determined by integrating the characteristic DADMA(PF 6 ) peaks and comparing values to those of the methyl proton peaks from the BPA‐type linkages (Figures 6 and S22–S24).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the relationship between tensile strength and ID are characterized in Figure 4b; the changes in the tensile strength and the ID of PI films with different chemical catalytic reagents show a consistent trend. The index of ID strongly correlates with the degree of in-plane orientation, mechanical strength, and thermal properties of PI film [41]. It can be concluded that the high tensile strength of PI films is attributed to the high imide degree and ordered aggregation phase.…”
Section: Structure and Properties Of Pi Filmsmentioning
confidence: 94%
“…1,8-diazabicyclo [5.4.0] undec-7-ene (DBU) was also effective to reduce the imidization temperature of PAA to 200 °C [ 23 , 24 ]. Huang C. et al [ 25 ] have investigated the mechanical, thermal, and electrical properties of the polyimide films derived from the imidization of PAA catalyzed by quinoline (QL) and quinoline derivatives. Sui, Y.Y.…”
Section: Introductionmentioning
confidence: 99%